Impulsive noise estimation and suppression in OFDM systems over in‐home power line channels. (9th July 2014) - Ahadiat, Mohammad Reza; Azmi, Paeiz; Haghbin, Afrooz
Summary: This paper proposes a new adaptive iterative method to impulsive noise mitigation in OFDM systems over in‐home power line channels. The performance of impulsive noise mitigation methods based on OFDM decreases when the impulsive noise energy is higher than a certain threshold. To compensate for the limitations of these systems and to be able to adopt it for all sub‐carriers, here, the 64‐QAM constellation is applied together with Alamouti space time coding to transmit, MIMO In‐home power line channel and zero‐forcing estimate (ZFE) with continuous loop impulsive noise detection and mitigation together with maximum‐likelihood detection (MLD) are adopted to receive. At the receiver, after ZFE, impulsive noise detection algorithm based on adaptive threshold for estimating the impulsive noise, determines the locations and amplitudes of the impulsive noises. The effect of impulsive noise on the noise symbols using the mask based on the soft decision method is reduced. Later, using MLD, the original signal is estimated. The algorithm is simulated and analyzed, and its performance is compared to other methods. The results show the superiority and robustness of the proposed method. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : This paper proposes a new adaptive iterative method to impulsive noise mitigation in Orthogonal Frequency Division Multiplexing systems over in‐home power line channels. The 64‐QAM constellation is applied together with Alamouti space time coding to transmit, MIMO in‐home power line channel and zero‐forcing estimate with continuous loop impulsive noise detection and mitigation together with Maximum‐Likelihood Detection are adopted to receive.